Creation of Bundengan Organology - A., Ghazian Arka Fikry; Wafa, Mochammad Usman (Jurnal Seni Musik, 2023)
Bundengan is a traditional musical instrument whose existence is still maintained and is also an icon of Wonosobo Regency. The music group Rungon Wresthi created the Bundengan organology in the Wonosobo Regency. This research aims to examine the organological creations carried out. This research uses qualitative methods with a musicological approach. Data was collected through direct interviews and documentation studies. Data analysis was carried out by reducing data, presenting data, and providing conclusions. The results of this research show that Rungon Wresthi is a music group dedicated to preserving Bundengan’s musical instruments. This music group carries out organological creations in the form of changes and developments in Bundengan musical instruments regarding design, materials, and how to play them. There are four types of Bundengan creations, each with its function or using instruments.